CRYSTAL CHEMISTRY OF DEFECT SUBSYSTEM OF NON- STOICHIOMETRIC LEAD TELLURIDE - Туровська, Лілія Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Quasiсhemical and crystal-quasiсhemical formulae of defect subsystem in nonstoichiometric PbTe crystals are offered. Values of equilibrium constants of quasichemical reactions of intrinsic point defects formation in lead telluride are revised. Using the method based on minimizing of the thermo dynamic potential of "crystal-pair" system as a function of defect concentration, equilibrium concentration of point defects and free charge carriers, depending on technological factors two-temperature annealing are calculated.